Analysis of the prefaces of the algebraic texts published in Spain during the 16th century - Muñoz-Escolano, Jose M.; Oller-Marcén, Antonio M. (Historia y Memoria de la Educación, 2019)
In this work, we use the historical research method to analyze the prefaces of those texts written in Spanish and published during the 16th century that had algebraic content. In particular, we have studied ten prefaces from six books written by four authors. The analysis is twofold. On one hand, we identify the general themes treated by the authors in the chosen fragments. On the other hand, we identify characteristics related to the authors’ conceptions and beliefs about different aspects related to the nature of mathematics, its teaching and its learning. The methodology used is of a qualitative nature and follows a deductive approach. A great variety of general topics have been identified both in the prologues addressed to the reader and in those addressed to a specific person, while the aspects related to conceptions and beliefs are mainly concentrated in the prefaces to the reader. The categories used cover practically all of the analyzed text. The most discussed topics are those related to the declarations of intentions, to veracity and to the questions of novelty or tradition. Regarding beliefs, the most discussed aspects are those related to the nature of mathematics, followed by those related to how to teach or learn mathematics.